Systematic Literature Review: Pengaruh Penggunaan Software Cabri 3d Pada Pembelajaran Matematika - Yasmin Salsabila; Yahfizham (Pusat Riset dan Inovasi Nasional, 2024)
Cabri 3D is a computer device is a medium of learning mathematics. This research aims to examine and determine the effects that arise in learning mathematics by utilising the use of Cabri 3D software. This research method is Systematic Literature Review (SLR). Data were collected through selecting 10 journal articles related to the use of Cabri 3D in learning mathematics using Google Scholar, Research Gate, SINTA and Garuda in the 2019-2023 time span. The results showed that there was an effect of Cabri 3D software in learning mathematics on improving the ability of concepts, understanding, reasoning, spatial, representation, mathematics knowledge competence and learning motivation of students.